(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
Tools can tell a lot about not only the lifestyle of an ancient person, but also about the peculiarities of his thinking. The ability to "read" stone, that is, to see the direction of blows, to separate the influence of the human hand from the influence of nature, is one of the most controversial topics among historical archaeologists today.